Kecerdasan Emosi dan Kecerdasan Kalbu dengan Pendekatan Tasawuf: Mewujudkan Keberagamaan yang Moderat - Rahayu, Endang Sri (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2022)
This study aims to review emotional intelligence and kalbu intelligence with a tasawuf (Sufism) approach in order to realize moderate religiosity. This is motivated by the religious phenomenon of some people or groups who often carry out anarchic actions against others under the pretext of "amar ma'ruf nahi munkar." This research uses a descriptive-analytical method through a qualitative approach. In this context, the author is of the view that the Sufism approach to religion is closely related to emotional intelligence and kalbu intelligence in humans. This study concludes that Sufism is useful in realizing moderate diversity so that it can prevent someone from judging others who are not in line with their religious views.